LaTeX workshop - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Chin, Mei Lee; Norhayati, Nordin; Siti Aisah, Harun; Nenie Zuryati, Abdullah; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras (Penerbit Universiti Malaysia Pahang, 2011)
A one-day LaTeX workshop was conducted on July 20 by the Faculty of Science & Technology Industry (FIST} at UMP Gambang. There were 29 participants from among FIST's academic staff and graduate students. Dr Roslinazairimah Zakaria conducted the workshop assisted by Dr Mohd Zuki Salleh and Pn Siti RoslindarYaziz.